استصلاح الأراضي عن طريق الامتياز في التشريع الجزائري - سالمي, ابتهاج; عمراني, عز الدين (My University, 2023)
أمام تناقص وعاء العقار الفلاحي اضطرت السمطة إلى تشجيع عمميات الاستصلاح، و التي شيدت ركود نسبي رغم التدابير التشجيعية المنصوص عمييا في القانون 18/83 15 الذي /12/ 97 المؤرخ في 1997 / ،وكذلك المرسوم التنفيذي رقم 483 يحدد كيفيات منح الامتياز في القطع الأرضية التابعة للأملاك الخاصة لمدولة في المساحات 21/ الاستصلاحية و أعبائو و شروطو و بقصد انتعاش الاستصلاح صدر المرسوم 432 الذي يحدد شروط وكيفيات منح الأ ا رضي التابعة للأملاك الخاصة لمدولة، للاستصلاح في إطار الامتياز،و قد عرفت المادة الثانية الإستصلاح بكل عمل يرمي إلى وضع حيز الإنتاج وتثمين قد ا رت الأملاك العقا رية ذات الوجية الفلاحية لمسماح بإنتاج سنوي أو متعدد السنوات الموجو للاستيلاك البشري أو الحيواني أو الصناعي مباشرة أو بعد تحويمو. و يتبين من د ا رسة أحكام ىذا المرسوم أن تشجيع الإستثمار يكون بمنح الأرض عن طريق عقد امتياز و بمقابل دفع أتاوة و تساىم الدولة بالنسبة لممشاريع التي تحظى بالأولوية بتوفير المياه و الطاقة الكيربائية وشق الطرق بالإضافة إلى الاستفادة من الامتيا ا زت المالية و الجبائية،In view of the decrease in the pot of the agricultural property, the authority was forced to encourage reclamation in spite of the encouraging measures provided for in Law 18/83, As well as Executive Decree No. 483/97 of 1997/12/15, which sets out the modalities for granting concessions in plots belonging to the private property of the State in reclamation spaces, its burdens and conditions, and with a view to the recovery of reclamation, Decree No. 432/21, which sets out the conditions and modalities for granting land belonging to the private property of the State. The second article defines reclamation as any work aimed at putting into production and valuing the capabilities of peasant-oriented real estate to allow for annual or multi-year production directed at human, animal or industrial consumption directly or after conversionIn view of the decrease in the pot of the agricultural property, the authority was forced to encourage reclamation in spite of the encouraging measures provided for in Law 18/83, As well as Executive Decree No. 483/97 of 1997/12/15, which sets out the modalities for granting concessions in plots belonging to the private property of the State in reclamation spaces, its burdens and conditions, and with a view to the recovery of reclamation, Decree No. 432/21, which sets out the conditions and modalities for granting land belonging to the private property of the State. The second article defines reclamation as any work aimed at putting into production and valuing the capabilities of peasant-oriented real estate to allow for annual or multi-year production directed at human, animal or industrial consumption directly or after conversion
مذكرة ماستر
Keywords: الإستصلاح، الإمتياز، الأ ا رضي الفلاحية، العقار الفلاحي، الإستثمار العقار; reclamation, concession, farmland, agricultural property, real estate investment.